2015
DOI: 10.1007/s11626-015-9919-6
|View full text |Cite
|
Sign up to set email alerts
|

Some ferrocenyl chalcones as useful candidates for cancer treatment

Abstract: Although knowledge of cancer management is extensive, mortality is not currently declining in this area. It is therefore important to implement a long-term strategy that would aim to prevent these serious diseases. Ferrocene-related organometallic compounds are promising candidates for design of new drugs since they can exhibit much greater biological activity than their phenyl analogs. In our work, we focused on investigating the cytotoxic and antiproliferative effects of five ferrocenyl derivatives toward se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Similar antifungal activities were reported by Muskinja et al for different ferrocenyl chalcones (Muskinja et al, 2016). Janka et al prepared novel ferrocenyl chalcones and screened their anti-cancer activities against HeLa, MCF7, A549 and MDA cells and reported that they have potential antitumor activity (Janka et al, 2015).…”
Section: Figure 1 Some Natural Compounds Containing Chalcone Unitsupporting
confidence: 71%
“…Similar antifungal activities were reported by Muskinja et al for different ferrocenyl chalcones (Muskinja et al, 2016). Janka et al prepared novel ferrocenyl chalcones and screened their anti-cancer activities against HeLa, MCF7, A549 and MDA cells and reported that they have potential antitumor activity (Janka et al, 2015).…”
Section: Figure 1 Some Natural Compounds Containing Chalcone Unitsupporting
confidence: 71%
“…In previous studies on various different ferrocene derivatives, some have been shown to exhibit surprisingly high toxicity and antiproliferative activity [32][33][34]. Among the unique derivatives available for study, the antiproliferative effect of the (E)-3-(ferroceneethylene)-4-chromanone was the most effective [35]. The pronounced effect of cell viability and colony formation of cancer cells in dose-dependent manner has been shown by 1,1′-bis[(1-oxoindane-2-ylidene) methyl] ferrocene.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the ferrocenyl unit was conjugated with known compounds possessing chemotherapeutic properties, e.g., adenine, , peptides, , nucleosides and nucleobases, , vitamins, , and phenols including taxoids (paclitaxel and docetaxel, antineoplastic agents), in order to have built-in efficacy. Thus, Fc as an effective bioisostere has provided a potential platform for drug design by virtue of its aforementioned properties and three-dimensional metallocene unit, which may lead to some alterations in selectivity toward biological targets, in comparison with phenyl or alkyl groups. , …”
Section: Introductionmentioning
confidence: 99%
“…Thus, Fc as an effective bioisostere has provided a potential platform for drug design by virtue of its aforementioned properties and threedimensional metallocene unit, which may lead to some alterations in selectivity toward biological targets, in comparison with phenyl or alkyl groups. 24,25 On the other hand, the last few decades have witnessed renewed research interest in organotin(IV) compounds, which poses diverse medicinal applications such as antiviral, antimicrobial, antiparasitic, antihypertensive, antihyperbilirubinemia, and anticancer activities, apart from their standard uses as biocides, catalysts, and stabilizers. 26−32 In comparison to standard drugs, the majority of organotin(IV) carboxylates discussed in the literature have shown superior anticancer activity against various cell lines.…”
Section: ■ Introductionmentioning
confidence: 99%